Analysis of the Application of the Wa‘d Concept in the Issuance Project Based Sukuk (PBS) in Indonesia - Kurniawan, Taufiq; Ab Rahman, Asmak (al-'adalah, 2021)
Indonesia, in recent years, has been trying to accelerate economic development, especially in the field of infrastructure development. This effort requires enormous funding, both from abroad and domestically. To expand funding sources from within the country, the government issued Project Based Sukuk (PBS) which aims to finance infrastructure development through sharia-based financing instruments. PBS is indeed an alternative for Muslim communities who are interested in building the country's economy without being overshadowed by the element of usury. This instrument has a main contract in the form of ijarah, supporting contracts and promises (wa'd). The application of these contracts can only be said to be valid from the point of view of the Shari'ah if all the rules and conditions are fully complied with. This study tries to analyze the application of the wa'd concept in PBS, to find out whether all the rules and conditions set by Syara' have been implemented properly. Data were collected through interviews and literature review which were then analyzed using a normative approach. This study concludes that the application of the al-wa'd concept to PBS is in line with sharia principles, although there are still two issues that still need to be fixed, namely first: the problem of investor ownership of PBS assets which is only for benefits, not accompanied by ownership of the goods; both mechanisms for reselling PBS assets at a price equivalent to the nominal value of PBS, even though according to AAOIFI and Majma' al-Fiqh al-Islāmī al-Duwali sukuk assets may not be resold at a price equivalent to the nominal value of the sukuk.